What Makes Consumption Experiences Feel Special? A Multimethod Integrative Analysis - Sun, Jennifer J; Pham, Michel Tuan (Journal of Consumer Research, 2026)
Abstract This article addresses a simple theoretical question of high substantive relevance: What makes a consumption experience special in a consumer’s mind? To answer this question, the authors report an extensive multimethod investigation involving a grounded theory analysis of numerous consumer narratives and in-depth interviews, a field survey, a scale development study, a natural language processing (NLP) analysis of more than 3 million Yelp reviews, a preregistered multifactor causal experiment (and its preregistered replication), a blind comparison of hundreds of matched visual Instagram posts by third-party observers, and several small application studies. The findings converge in identifying three major psychological pillars of what makes consumption experiences feel special to consumers, each pillar involving different facets: (a) uniqueness, which arises from the rarity, novelty, irreproducibility, personalization, exclusivity, ephemerality, and surpassing of expectations of the experience; (b) meaningfulness, which pertains to the personal significance of the experience in terms of symbolism, relationships, self-affirmation, and self-transformation; and (c) authenticity, which relates to the perceived genuineness and realness of the experience in terms of its psychological proximity to some original source, iconicity, human sincerity, and connection to nature. As illustrated in the General Discussion, the findings have important substantive implications for the engineering of hedonic consumption experiences.